2014
DOI: 10.1002/ejoc.201403237
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tetrasubstituted Symmetrical Pyrazines from β‐Keto γ‐Amino Esters: A Mild Strategy for Self‐Dimerization of Peptides

Abstract: A facile synthesis of highly symmetrical tetrasubstituted pyrazines through simple aerial oxidation of β‐keto γ‐amino esters is reported. The scope of the reaction was examined by use of various amino acid side‐chain functional groups and peptides. The mild and efficient transformation of β‐keto γ‐amino esters into pyrazines may serve as an attractive strategy for self‐dimerization of peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…To address the racemization issue, we hypothesized that bypassing an activated carboxylic acid to obtain the β-ketoester intermediate would eliminate the propensity for enolization. We adopted the method of Mothukuri et al to generate β-ketoesters from phenylglycinal ( 27 ) by treating it with ethyl diazoacetate in the presence of the Lewis acid SnCl 2 [ 30 , 31 ]. Starting from the optically pure S-phenylgylcinol, a Dess–Martin oxidation was performed to generate 27 , which was then submitted to the procedure advanced by Mothukuri et al to afford 28 in a 64% yield ( Scheme 4 ) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the racemization issue, we hypothesized that bypassing an activated carboxylic acid to obtain the β-ketoester intermediate would eliminate the propensity for enolization. We adopted the method of Mothukuri et al to generate β-ketoesters from phenylglycinal ( 27 ) by treating it with ethyl diazoacetate in the presence of the Lewis acid SnCl 2 [ 30 , 31 ]. Starting from the optically pure S-phenylgylcinol, a Dess–Martin oxidation was performed to generate 27 , which was then submitted to the procedure advanced by Mothukuri et al to afford 28 in a 64% yield ( Scheme 4 ) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…We adopted the method of Mothukuri et al to generate β-ketoesters from phenylglycinal ( 27 ) by treating it with ethyl diazoacetate in the presence of the Lewis acid SnCl 2 [ 30 , 31 ]. Starting from the optically pure S-phenylgylcinol, a Dess–Martin oxidation was performed to generate 27 , which was then submitted to the procedure advanced by Mothukuri et al to afford 28 in a 64% yield ( Scheme 4 ) [ 30 ]. To our delight, we confirmed that 28 was formed in greater than >99% ee (see Supplementary Materials ).…”
Section: Resultsmentioning
confidence: 99%
“…Typical methods for the preparation of pyrazines involve condensation of vicinal diamines with α-diketones followed by dehydrogenation or autocondensation of α-amino ketones . In addition to these methods, pyrazines have been synthesized using different classes of starting materials such as α-hydroxy ketones, α-halo ketones, α-halo enol acetates, nitro epoxides, 2 H- azirines, and β-keto γ-amino esters . Other strategies include Suzuki–Miyaura reactions of tetrachloropyrazine, biocatalytic reduction of β-keto α-oximino ester with Baker’s yeast, two-step synthesis via epoxide opening with β-amino alcohol followed by Swern oxidation, and ruthenium pincer complex catalyzed dehydrogenative condensation of β-amino alcohols .…”
Section: Introductionmentioning
confidence: 99%